Properties of flat-spectrum radio-loud narrow-line Seyfert 1 galaxies (Corrigendum) - Foschini, Luigi; Kaufmann, Sarah (Astronomy and astrophysics, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics
Gesehen am 11.10.2017